Changes in the chlorophyll content of grape leaves could provide a physiological index for responses and adaptation to UV‐C radiation. (1st May 2019) - Luo, Y. Y.; Li, R. X.; Jiang, Q. S.; Bai, R.; Duan, D.
Abstract : Stilbenes are a group of phytoalexins that play an important role in grapevine ( Vitis ) basal immunity and can be induced by biotic and abiotic stresses. The levels of chlorophylls, the main pigments in plant cells, can also indicate the tolerance of plants to various stresses. Here, the response of different grapevine genotypes to UV‐C radiation treatment was tested and the abundance of chlorophyll in the Hoe29 and Ke53 genotypes was observed to increase significantly within 6 h of UV‐C treatment. Conversely, chlorophyll levels decreased markedly in the Augster Weiss and Müller–Thurgau genotypes. Furthermore, stilbene abundance increased substantially in the Hoe29, Ke53, Ke83 and Pinot Blanc genotypes, but increased only slightly in Augster Weiss and Müller–Thurgau. The expression of resveratrol synthase, which encodes a key enzyme in the stilbene synthesis pathway, increased in Hoe29, Ke53, Ke83 and Pinot Blanc following UV‐C treatment, in a manner consistent with stilbene accumulation. In addition, we observed that reactive oxygen species (ROS) provide a key trigger in physiological responses and changes in secondary metabolite contents. In summary, the results from this study support a link between ROS, chlorophyll levels and genetic diversity for stilbene abundance in different grape genotypes, providing insights into mechanisms for plant physiological and biochemical responses and adaptations to stress.